HUBUNGAN PERSEPSI SISWA TERHADAP KREATIVITAS GURU DALAM MENGAJAR DENGAN MINAT BELAJAR MATEMATIKA DI KELAS V SDN 167 PEKANBARU - HarLonny, Desma Fujy; Syahrilfuddin, Syahrilfuddin; Guslinda, Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine whether there is a significant relationship between students' perceptions towards teacher creativity in teaching with interest in learning mathematics in class V SDN 167 Pekanbaru. This research was conducted in Pekanbaru SDN 167 in January 2019, this research is a quantitative study with a sample of 40 students. The data used in this study are primary data obtained from questionnaire data. Data collection techniques were obtained from student perception questionnaires towards teacher creativity in teaching and mathematics learning interest questionnaires given to students. Data were analyzed by statistical techniques using SPPS Version 23. Software Based on data analysis, the results of the study showed that there was a significant relationship between student perceptions towards teacher creativity in teaching with fifth grade mathematics interest in SDN 167 Pekanbaru with a contribution of 30.9%.Key Words: Student perception, teacher creativity, interest in learning